Modernisasi Administrasi Publik melalui Implementasi Sistem Informasi Manajemen Puskesmas: Tinjauan Literatur Sistematis Metode Prisma - Satmawati Satmawati; Jamaluddin Hos (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The modernization of public administration is a strategic agenda for improving the quality of governance, particularly in the primary healthcare sector, which plays a direct role in delivering services to the community. One of the key instruments in this process is the implementation of the Community Health Center Management Information System (SIMPUS), which aims to enhance service efficiency, data management accuracy, and the quality of information-based decision-making. This study aims to analyze the readiness and effectiveness of SIMPUS implementation in supporting the digital transformation of public services at the primary healthcare level. The method used is a systematic literature review employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach on 15 scientific articles published between 2014 and 2024. The findings indicate that SIMPUS implementation consistently contributes to improved administrative efficiency, better health data quality, and enhanced accessibility of service information. However, several challenges remain, including limited technological infrastructure, low human resource capacity, and resistance to organizational change. Policy limitations and weak inter-institutional coordination also affect implementation success. Therefore, a comprehensive digital transformation strategy is required through strengthening human resource competencies, enhancing managerial support, and integrating information systems across government sectors to support optimal and sustainable healthcare services.